Global business discourse – reflections from a cultural nomad / Jonathan A.J. Wilson. - Wilson, Jonathan A.J. (Universiti Teknologi Mara Selangor, 2013)
The purpose of this paper is to document and disseminate the full experiences of the author following a series of events hosted by UiTM MARA, Shah Alam, Selangor; and attending World Halal Week, Kuala Lumpur, in Malaysia; during the first week of April 2013. The paper shares the content and key findings presented at these events, which took the form of a workshop, guest lecture, keynote, and panel session; and is supported by further reflective narratives, analogies and allegories. The underpinning methodological approach has been termed an ‘Eagle Eye Gestalt’, which presents an innovative approach to antipostivist phenomenological analysis, rooted in Consumer Culture Theory (CCT). The key arguments presented are that global business discourse, for both practitioners and academics, necessitate the championing and implementation of 21st century Culture, Branding, and Transformational Leadership strategically. Furthermore, consideration should be given to nurturing an environment, which is conducive to facilitating inspiration, social interactions, and networking opportunities – all with an intended purpose dictated by business imperatives.